LOWERING CARDIOVASCULAR RISK FACTORS ASSOCIATED WITH DIABETES IS POSSIBLE USING THE EXTRACT OF URTICA PILULIFERA LEAVES - Ahed J Al Khatib; Osama Ahmad Alkouri; A. B. Maikano; S. M. Shuaibu; Sani S. Bashir; Surayya L. Idris; Fatima A. Shuaibu; Ilham A Al khatib; Fatima Laiche (European Scientific Journal, ESJ, 2014)
Diabetes mellitus is associated with increased cardiovascular risk factors, and such factors are attributed to disturbances in lipid profile. The present study was conducted to show the direct effect of diabetes on lipid profile in rats with diabetes using alloxan induced diabetic model and to investigate the possible therapeutic effects of using Urtica pilulifera . Methodology followed included collection and processing of Urtica pilulifera leaves, induction of diabetic rat model and investigating the effects of Urtica pilulifera on lipid profile of diabetic group. Study findings showed that in control group, the levels of triglyceride, total cholesterol, and LDL-C increased significantly (P<0.05), whereas the level of HDL-C decreased significantly (P<0.05) compared with control group. Treatment with the extract of Urtica pilulifera leaves using 1.25g/kg/body weight, or 1.88 g/kg body weight decreased the levels of triglyceride, total cholesterol, and LDL-C (P<0.05) compared with diabetic group, whereas the level of HDL-C increased significantly compared with diabetic group (P<0.05). Taken together, the present study showed that diabetes is a possible risk factor for cardiovascular disease through induction of disturbances in lipid profile. Treatment using the methanolic extract of Urtica pilulifera leaves reversed the adverse effects of diabetes and restored lipid profile to control level.